Optineurin deficiency in mice is associated with increased sensitivity to Salmonella but does not affect proinflammatory NF‐κB signaling. Issue 4 (15th January 2016) - Slowicka, Karolina; Vereecke, Lars; Mc Guire, Conor; Sze, Mozes; Maelfait, Jonathan; Kolpe, Annasaheb; Saelens, Xavier; Beyaert, Rudi; van Loo, Geert
Abstract : Identification of Optineurin's in vivo functions through mouse gene targeting studies .Karolina Slowicka, Lars Vereecke, Conor Mc Guire, Mozes Sze, Jonathan Maelfait, Annesaheb Kolpe, Xavier Saelens, Rudi Beyaert and Geert van Loo To assess the in vivo functions of OPTN in inflammation and infection, we generated OPTNdeficient mice, and analysed their phenotype in conditions of NF‐κB and type I interferon signaling, and in the innate immune response against bacteria. Abstract : Optineurin (OPTN) is an evolutionary conserved and ubiquitously expressed ubiquitin‐binding protein that has been implicated in glaucoma, Paget bone disease, amyotrophic lateral sclerosis, and other neurodegenerative diseases. From in vitro studies, OPTN was shown to suppress TNF‐induced NF‐κB signaling and virus‐induced IRF signaling, and was identified as an autophagy receptor required for the clearance of cytosolic Salmonella upon infection. To assess the in vivo functions of OPTN in inflammation and infection, we generated OPTN‐deficient mice. OPTN knockout mice are born with normal Mendelian distribution and develop normally without any signs of spontaneous organ abnormality or inflammation. However, no differences in NF‐κB activation could be observed in OPTN knockout mice or fibroblasts derived from these mice upon TNF or LPS treatment. Primary bone marrow‐derived macrophages from OPTN‐deficient mice had slightly impaired IRF signaling and reduced IFN type I production in response to LPS or poly(I, C). Finally, OPTN‐deficient mice were more susceptible to infection with Salmonella, confirming in vivo the importance of OPTN in bacterial clearance.